Constructions of space IV: further developments in examining ancient Israel's social space - George, Mark K. (Library of Hebrew Bible / Old Testament studies, 2013)
Critical studies and analyses of space are becoming increasingly common in scholarship, although it is not always clear how such studies proceed, what theoretical works inform them, or what are their potential benefits for biblical studies. This volume helps address those questions, by including the work of biblical scholars working in a range of historical periods and locations, from Deuteronomy's idealized spaces to the Qumran community on the shores of the Dead Sea. Each of the scholars in this volume is actively involved in the critical study of space, having presented work on this topic i